InP nanowires grown by SA-MOVPE - Gao, Q; Tan, H; Fu, L; Parkinson, P; Breuer, S; Wong-Leung, J; Jagadish, C (2012)
A systematic growth temperature study has been performed to achieve high quality InP nanowires (NWs) by selective-area metal-organic vapour-phase epitaxy (SA-MOVPE). The optical quality of these nanowires was evaluated from time-resolved photoluminescence (TRPL) at 300 K. © 2012 IEEE.